Pengelolaan Aplikasi SINDE dalam Arsiparis di Balai Penjaminan Mutu Pendidikan Provinsi Kalimantan Tengah - Khairunnisa Khairunnisa; Sapuadi Sapuadi (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
The purpose of this research is to find out how the sinde application is managed in archivist activities at the Central Kalimantan provincial education quality assurance center. The approach used in this research is a descriptive qualitative approach. The data source in this research is the documents management employee at the Central Kalimantan provincial education quality assurance center. The data collection technique used in this research is through interviews, observation and documentation. The data collection technique is through data reduction and presentation as well as drawing conclusions. The results of this research show that the management of the Sinde application is very relevant and effective for archivist activities in the Central Kalimantan province education quality assurance center. This can shorten time, can be accessed anywhere using the username and password owned by each employee can save use of physical paper and save time, letters can be accessed through the sinde application, you can see incoming letters, outgoing letters and can classify letters based on type, date and so on.